Mobile forensic investigations : a guide to evidence collection, analysis, and presentation - Reiber, Lee (New York : McGraw-Hill Education, 2016)
"Conduct mobile forensic investigations that are legal, ethical, and highly effective using the detailed information contained in this prac tical guide. Mobile Forensic Investigations: A Guide to Evidence Collec tion, Analysis, and Presentation fully explains the latest tools and me thods along with features, examples, and real-world case studies. Find out how to assemble a mobile forensics lab, collect prosecutable eviden ce, uncover hidden files, and lock down the chain of custody. This comp rehensive resource shows not only how to collect and analyze mobile dev ice data but also how to accurately document your investigations to del iver court-ready documents"--
Machine generated contents note: Chapter 1: Introduction to the Worl d of Mobile Device Forensics -- Chapter 2: Mobile Devices versus Comput er Devices in the World of Forensics -- Chapter 3: Evidence Collection at the Scene: USB Drives, SD Cards, SIM Cards, and Mobile Devices -- Ch apter 4: Bagging and Tagging Digital Evidence -- Chapter 5: Toolbox For ensics -- Chapter 6: Mobile Forensic Tool Overview -- Chapter 7: Prepar ing for Your First Collection: Preparing the Environment -- Chapter 8: Conducting a Collection of a Mobile Device: Considerations and Action - - Chapter 9: Analyzing SIM Cards -- Chapter 10: Analyzing Feature Phone s, BlackBerry and Windows Phone Data -- Chapter 11: Advanced iOS Analys is -- Chapter 12: Querying SQLite and Taming the Forensic Snake -- Chap ter 13: Advanced Android Analysis -- Chapter 14: Presenting the Data as a Mobile Forensic Expert.
Keywords: Computer crimes -- Investigation; Mobile communication systems; Forensic sciences; COMPUTERS / Security / General